Fatigue behaviour and damage characterization of quasi-isotropic carbon/epoxy laminates. Issue 1 (31st December 2022) - N H, Padmaraj; Pai K, Dayananda; Shreepannaga, Shreepannaga; Kini, M Vijaya
Abstract: The present research work focuses on understanding the tension-tension fatigue durability of autoclave cured carbon/epoxy quasi-isotropic laminates. Based on the experimental results, S-N curve and stiffness degradation behaviour were developed. Damage growth mechanisms were studied based on the energy dissipated in each loading cycle at different stress levels. C-Scan and Scanning Electron Microscope were used to characterize the micro-crack growth and nature of fatigue failure. A bilinear trend was observed in the stress–strain curve with the failure of 90° oriented fibres in the initial phase followed by 0° oriented fibres. The energy dissipated and damage growth of the laminates at different stress levels followed a characteristic damage state curve. The C-Scan images showed the initiation of cracks on the specimen edges and propagating towards the center in the transverse direction.